Between two fires - Buehlman, Christopher (Tor Publishing Group, 2026)
"Enter a darker age with USA Today bestselling author Christopher Buehlman's Between Two Fires, a medieval horror adventure unlike anything on the shelf. And Lucifer said: "Let us rise against Him now in all our numbers, and pull the walls of Heaven down..." The year is 1348. Thomas, a disgraced knight, has found a young girl alone in a dead Norman village. An orphan of the Black Death, and an almost unnerving picture of innocence, she tells Thomas that plague is only part of a larger cataclysm-that the fallen angels under Lucifer are rising in a second war on heaven, and that the world of men has become their battleground. Is it delirium or is it faith? Now she has convinced the faithless Thomas to shepherd her across a depraved landscape to Avignon. There, she tells Thomas, she will fulfill her mission: to confront the evil that has devastated the earth, and give him-blood-stained and wretched as he is-a chance at redemption he long thought lost. As hell unleashes its wrath, and as the true nature of the girl is revealed, Thomas will find himself on a macabre battleground of angels and demons, saints and the risen dead, and in the midst of a desperate struggle for nothing less than the soul of man"-- Provided by publisher.